2019
DOI: 10.1186/s12870-019-1868-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the blast resistance of the elite rice variety Kongyu-131 by updating the pi21 locus

Abstract: Background As an elite japonica rice variety, Kongyu-131 has been cultivated for over 20 years in the third accumulated temperature zone of Heilongjiang Province, China. However, the cultivated area of Kongyu-131 has decreased each year due to extensive outbreaks of rice blast. To achieve the goals of improving blast resistance and preserving other desirable traits in Kongyu-131, a genome-updating method similar to repairing a bug in a computer program was adopted in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In tomato, the linkage breakdown of nematode resistance and undesirable fruit characteristics took 12 years to separate (Acquaah, 2012). However, in rice blast resistance, linkage drag was effectively removed in two cycles of recombinant selection (Feng et al, 2019). Cao et al (2010) reported that backcross breeding and marker-assisted selection are effective tools to break linkage drag between low oil content and erucic acid in canola cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, the linkage breakdown of nematode resistance and undesirable fruit characteristics took 12 years to separate (Acquaah, 2012). However, in rice blast resistance, linkage drag was effectively removed in two cycles of recombinant selection (Feng et al, 2019). Cao et al (2010) reported that backcross breeding and marker-assisted selection are effective tools to break linkage drag between low oil content and erucic acid in canola cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional MAS may result in the introduction of undesirable genes, or loss of desirable traits with unclear genetic backgrounds. In addition to foreground selection, background selection is essential as it is more accurate and e cient (Feng et al 2019). Recently, a Bnapus50K array that provides precise genomic information on Chinese local accessions of B. napus was developed (Xiao et al 2021).…”
Section: High Recovery Ratio Of Recurrent Parent Genome To Shorten Th...mentioning
confidence: 99%
“…Unlike most blast R genes, Ptr , which is required for broad-spectrum blast resistance mediated by R genes Pita and Pita2 , encodes a four Armadillo (ARM) repeat protein. Furthermore, more alleles or natural variation of broad-spectrum blast resistance R genes have been investigated, including geographically distinct and domain-specific sequence variations of Pib , novel alleles of Pik locus Pi1 , Pike, and Pikg , Pi54 alleles, novel Pi21 haplotypes, and novel alleles of Pi2/9 locus [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In addition, four broad-spectrum resistance R genes, Pi-hk1 , Pi57 ( t ), Pi65 ( t ), and Pi69 ( t ), were finely mapped in the past 10 years [ 23 , 24 , 25 , 26 ].…”
Section: Identified Rice Broad-spectrum Disease Resistance Genes In Past 10 Yearsmentioning
confidence: 99%